Moving from Analysis to Assessment: Strategic Assessment of Library Collections. Issue 4 (18th May 2016) - Johnson, Qiana
ABSTRACT: Collections are one of the core resources provided by libraries and are often seen as what defines a library. Collection policies and priorities are put into place to guide the growth of libraries' collections. However as time passes, are the collections created best suited to the current patron population? Collection assessment can be used to evaluate how well the developing collection follows the guidelines that have been put into place. Collection assessment can also be beneficial in the library strategic planning process by identifying strengths and weaknesses in the collection, particularly in new areas of interest. It can also help identify areas that may need additional funding to continue the level of support previously maintained for an area.